Safety and Immunogenicity of the Tetravalent Recombinant COVID-19 Protein Vaccine SCTV01E in Children and Adolescents Aged 3 to 17 Years: A Randomized, Double-Blind, Placebo-Controlled Phase 2 Clinical Trial - Fengcai Zhu; Ting Huang; Pengfei Jin; Linglin Zhang; Zhongqiang Jin; Wenli Zhang; Dongya Yuan; Zhong Wang; Yusong Deng; Jiaxin Li; Xiao Shen; Yongpan Fu; et al. (Vaccines)
Background: SCTV01E is a tetravalent recombinant COVID-19 vaccine authorized for emergency use in China for adults 18 years and older but not for those under 18. Objective: This Phase 2 trial assessed the safety and immunogenicity of SCTV01E in healthy children and adolescents aged 3 to 17 years, to establish immunobridging with that observed in adults from the efficacy pivotal trial (NCT05308576). Methods: Participants were randomly assigned to receive either 30 µg of SCTV01E or a placebo. Primary endpoints were safety and immunogenicity focused on the geometric mean titer (GMT) and seroresponse rate (SRR) of neutralizing antibodies (nAb) against Omicron BA.5. Results: In total, 268 participants (214 SCTV01E vs. 54 placebo) were included in the safety analysis, with 241 participants (191 vs. 50) in the immunogenicity analysis. Overall, 127 (59.3%) participants receiving SCTV01E and 9 (16.7%) receiving a placebo reported adverse events (AEs), most of which were Grade 1 or 2. No serious adverse events (SAEs) or adverse events of special interest (AESIs) were reported. In the immunogenicity bridging analysis, data from 95 youths were compared with data from 188 adults; the geometric mean ratio (GMR) of the titers was 8.78 (95% CI: 6.05–12.74, p < 0.001), with the lower bound of the 95% CI exceeding 0.67. The difference in the SRR was 6.34% (95% CI: 0.93–11.22%) (p = 0.029), and the lower bound of the 95%CI was >−5%, indicating superiority. Conclusions: SCTV01E was found to be safe and well tolerated in children and adolescents, generating a robust immune response against Omicron BA.5. This supports its potential use in younger populations.